Product design: Metal nanoparticle‐based conductive inkjet inks. Issue 8 (16th May 2016) - Tam, Sze Kee; Fung, Ka Yip; Poon, Grace Sum Hang; Ng, Ka Ming
Abstract : A systematic procedure that provides an efficient workflow for formulating conductive inks is developed. Qualitative product attributes of the inkjet ink are first identified and transformed into quantitative product specifications. Ingredients are then selected based on heuristics, mechanistic, and empirical models to meet the product specifications. Printability checks based on theoretical criteria are used to ensure that stable droplets can in principle be formed and coalesced properly to form a printed line of ink. Then, the conductive ink is prepared and printed to evaluate the performance of the inkjet ink experimentally. An example of preparing a copper ink for inkjet printing is used to illustrate the systematic procedure. © 2016 American Institute of Chemical Engineers AIChE J, 62: 2740–2753, 2016